The Role of Public Policy in Shaping High-Impact E-Learning Practices and Their Effect on the Quality of Education - Wail Shafi Alshammari; Abdulrahman Eidhah Al Shamlan; Asmahan Ibrahim Alsalman; Ahmed Ibrahim Hassan Ibrahim; Mohamed Eid Kilase Ajoud (European Journal of Sustainable Development, 2025)
This study investigates the role of public policy in shaping high-impact e-learning practices (HIPs) and their influence on the quality of education from the perspective of faculty members. Building on a structural model, the research tests five hypotheses related to key HIPs, including community-based learning, common intellectual experiences, faculty guidance, first-year experiences, and university research initiatives. The findings reveal that only two of the proposed high-impact practices—common intellectual experiences and university research—exhibit a statistically significant positive relationship with perceived educational quality. In contrast, no significant association was found with community-based learning, faculty guidance, or first-year experience. Specifically, the hypothesis related to university research (H5) demonstrated the strongest support (t = 12.156, p = 0.000), indicating a robust impact on quality outcomes. Common intellectual experiences (H2) also showed a significant effect (t = 3.876, p = 0.000), underscoring their value in enhancing educational outcomes. The results suggest that public policies aimed at strengthening institutional research agendas and fostering integrative intellectual environments are more likely to drive improvements in educational quality, as perceived by faculty. Conversely, certain widely promoted HIPs may not yield measurable gains unless they are better aligned with institutional strategies or faculty engagement models. This research underscores the necessity of evidence-based policy-making that prioritizes pedagogical practices with demonstrable impact, particularly within e-learning environments shaped by digital transformation and post-pandemic reforms. Keywords: Public Policy, High-Impact Practices (HIPs), E-Learning, Educational Quality, Faculty Perspective, University Research, Common Intellectual Experiences, Digital Education, Higher Education Policy, Teaching Effectiveness